Screen natural terpenoids to identify potential Jab1 inhibitors for treating breast cancer - Pandey, Pratibha; Khan, Fahad; Yadav, Kiran; Singh, Kartikey; Rehman, Akhlakur; Mazumder, Avijit; Ahmad Khan, Minhaj (Trends in Immunotherapy, 2023)
Jab1 (c-Jun activation domain-binding protein-1) overexpression has been extensively linked to cancer development (or metastasis) in various malignancies by positively regulating cancer cell proliferation or inactivating several tumor suppressors. Recent research has focused on utilizing plant products to target crucial elements of dysregulated signaling pathways to elucidate a potent cancer therapeutic approach. Terpenoids have shown significant anti-inflammatory and anti-cancerous properties in a broader range of carcinomas by inducing apoptosis. Through an extensive literature search, we have selected only those terpenoids (from the NPACT database) that have not been explored against Jab1 (CSN5, COP9 signalosome subunit 5) in breast cancer for our research study. We have used two docking servers, PATCH DOCK, and CB DOCK, to find the binding interaction between selected terpenoids and Jab1. Further, we have also used SWISS ADME to investigate the pharmacokinetics of selected ligands. Amongst all selected ligands, lutein (belongs to the xanthophylls class) has displayed maximum binding energy in both CB Dock and Patch Dock analysis. Hence, our preliminary in silico results have shown lutein as the potent lead candidate for developing a better drug against breast cancer. However, more in silico and in vitro studies are still needed to validate the inhibitory potential of lutein terpenoid against Jab1 in breast cancer.